Association Between Medial Displacement of the Middle Glenohumeral Ligament and Subscapularis Tear Severity. Issue 4 (4th April 2022) - Hsu, Kai-Lan; Chuang, Hao-Chun; Chang, Hao-Ming; Yeh, Ming-Long; Kuan, Fa-Chuan; Chen, Yueh; Hong, Chih-Kai; Su, Wei-Ren
Background: The intraoperative invisible middle glenohumeral ligament (MGHL) test has been shown to be associated with a subscapularis tendon retraction. However, the preoperative location of the MGHL and its association with subscapularis tear severity has not been evaluated. Purpose: To determine (1) the interrater reliability for identification and position of the MGHL, (2) any association between the MGHL position and subscapularis tears, and (3) the cutoff point at which MGHL position can predict subscapularis tear severity. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: The magnetic resonance imaging (MRI) scans and surgical records of 176 patients were retrospectively reviewed by 3 independent orthopaedists. MGHL's identification, level (its position on axial MRI), and medial retraction ratio (distance from the lesser tuberosity to the MGHL divided by the width of the glenoid) were documented, and the interobserver agreement of the 3 indices was assessed. We calculated the association between subscapularis tears and the MGHL level and medial retraction ratio. Receiver operating characteristic (ROC) curve analyses were conducted to establish the optimal threshold of the MGHL medial retraction ratio to predict subscapularis tear. Results: The MGHL was identified by at least 2 reviewers in 124 individuals (70.5%). The interobserver reliability was very good for MGHL identification (κ = 0.766), moderate for MGHL level (κ = 0.582), and excellent for MGHL medial retraction ratio (intraclass correlation coefficient = 0.848). A low, positive correlation between MGHL level and subscapularis tear severity was found (Somers d = 0.392, P < .001), as well as a significant association between the medial retraction ratio and Lafosse classification of subscapularis tear size ( P < .001). A medial retraction ratio of ≥1.25 had a sensitivity of 0.70, a specificity of 0.83, and a positive likelihood ratio of 4.20, with excellent accuracy (area under the ROC curve = 0.820) to predict severe subscapularis tear. Conclusion: The MGHL was identified in 70.5% of shoulder MRIs. The location of the MGHL on preoperative MRI, as described by its level and the medial retraction ratio, was significantly associated with subscapularis tear severity, and a medial retraction ratio of ≥1.25 was predictive of a severe subscapularis tear.